Wacana Multimodalitas Budaya: Tautan Peran Gender dan Akomodasi Komunikasi dalam Film Serial Gadis Kretek - Lulu Nadya Hakim; Teresa Metta Rosario; Rustono Farady Marta; Hana Rochani Gustasari Panggabean (Jurnal Riset Komunikasi (JURKOM), 2024)
Gadis Kretek (Lit. Cigarette Girl) is a film series that narrates the tale of Lebas and Arum, who embark on a quest to uncover the truth about a woman named Dasiyah (Jeng Yah). The series features two distinct periods: in 1946, when Dasiyah and Soeraja met during the development of the cigarette industry, and in 2001 when Lebas and Arum's search for Dasiyah revealed her family's past. This study analyzes the discourse of gender roles and communication accommodation in the Gadis Kretek film series, specifically episodes 1 and 2, using modality discourse analysis. The research method employed is qualitative, with speech analyzed through modality using elements of gender role theory and communication accommodation. The analysis of gender roles and communication accommodation in the Gadis Kretek film series, episodes 1 and 2, was conducted using Theo Van Leeuwen's Multimodality Discourse Analysis (MDA) method. The results of multimodal analysis indicate that in societies with traditional gender role views, communication tends to diverge or accentuate differences between parties. In contrast, in modern societies with non-traditional views, communication tends to be more open, reducing existing differences.